Steal induction in preschool children: is melatonin as good as clonidine? A prospective, randomized study. Issue 4 (2nd January 2013) - Almenrader, Nicole; Haiberger, Roberta; Passariello, Maurizio; Lonnqvist, Per‐Arne
Summary Objectives/Aims To investigate whether melatonin would be an alternative drug to clonidine for performance of steal induction. Background Distress during induction might have a negative impact on postoperative behavior. A steal induction is a technique for smooth anesthesia induction, and clonidine has been the primary agent for this purpose. There are conflicting results regarding the efficacy of melatonin for premedication, but its sleep inducing properties have been shown in children. Methods Pediatric patients ASA I and II were randomly assigned to receive either melatonin 0.3 mg·kg−1 or clonidine 4 μg·kg−1 orally. Primary outcome was the percentage of successful steal induction, while secondary outcomes were onset of sleep, overall quality of mask induction, and adverse events at emergence from anesthesia. Results A total of 87 patients were included for analysis with a median age of 33 months (range, 12–71) and median weight of 14 kg (range, 8–26). A successful steal induction was performed in 88.4% of group C and 75% of group M (P > 0.05). Onset of sleep in these patients occurred after a median time of 45 min (range 10–60) in group C and 35 min (range 15–60) in group M (P > 0.05). Children not falling asleep after melatonin received the premedication at a significantly earlier time point compared to those falling asleep (P = 0.001). Conclusions Melatonin was effective for steal induction in 75% of children compared to 88% of children who had clonidine. Melatonin resulted less effective when administered early in the morning.